Risk factors of breast cancer-related lymphedema - Uğur, Saadet; Arıcı, Cumhur; Yaprak, Muhittin; Mesci, Ayhan; Arıcı, Gülbin Ayşe; Dolay, Kemal; Özmen, Vahit (Mary Ann Liebert Inc, 2013)
Introduction: Secondary lymphedema is one of the major important long-term complications of breast cancer treatment. The aim of this study is to determine patient- and treatment-related risk factors of lymphedema in breast cancer patients. Patients and Methods: Patients, who had been operated on for primary breast cancer at Akdeniz University Hospital and followed regularly between August 1984 and December 2009 were included in the study. In order to evaluate the arm swelling objectively, measurements were performed with a flexible tape measure for both arms, and limb volume was calculated using a truncated cone volume formula. Participants, whose volume difference between the two arms was >= 5%, were considered as lymphedema-positive patients. The SPSS program (SPSS inc. Chicago, IL) was used for statistical analysis. Results: The mean age of 455 patients was 50.6 years and the median follow-up time was 53 months. Lymphedema was found in 124 (27%) patients. Most of the patients with a history of postoperative wound infection (52%) and lymphangitis (57%) had lymphedema (p = 0.003 and p = 0.002, respectively). Addition of radiation therapy increased lymphedema risk 1.83 times (p = 0.007). The mean duration of the axillary drainage and number of the removed lymph nodes were 7.8 days and 19, respectively. The rate of lymphedema in patients with early stage breast cancer was less than patients with advanced breast cancer (24% and 35.3%, respectively, p = 0.018). Most of the patients (92%) with lymphedema had a high body mass index (BMI >= 25 kg/m(2)), and obesity was another important factor for lymphedema (p < 0.001). Conclusions: The most important treatment and patient-related risk factors for breast cancer-related lymphedema were obesity (>= 25 kg/m(2)), axillary lymph node dissection, postoperative radiotherapy, wound infection, history of lymphangitis, and duration of axillary drainage. Elimination or prevention of these risk factors may reduce the incidence of lymphedema.
WOS: 000320503900003
PubMed ID: 23772716
Keywords: Risk Factors; Breast Cancer Related; Lymphedema